2023
DOI: 10.1177/15271544231201417
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices for Telehealth in Nurse-Led Care Settings—A Qualitative Study

Charlotte R. Weiss,
Mia Roberts,
Melissa Florell
et al.

Abstract: The COVID-19 pandemic in the US prompted a sudden shift to telehealth in nurse-led care sites which provide services to diverse geolocations. Using a lens of intersectionality, this study characterizes provider and patient-perceived best and promising practices emerging from geographical variation. The aim of this study was to identify best practices of implementing telehealth in nurse-led care models in Colorado through patient and provider experiences of the sudden implementation of telehealth that can enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Findings from this study are largely consistent with what has been reported elsewhere. 17 , 18 , 32 Virtual care existed pre-pandemic but was not widely adopted and the imposition created by the pandemic necessitated everyone to quickly open up to the possibility of this as a viable mode of healthcare delivery. 17 The positive attitudes among both physicians and patients reflect findings from work that predated the pandemic and have been found in numerous other studies done across a variety of settings and health conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from this study are largely consistent with what has been reported elsewhere. 17 , 18 , 32 Virtual care existed pre-pandemic but was not widely adopted and the imposition created by the pandemic necessitated everyone to quickly open up to the possibility of this as a viable mode of healthcare delivery. 17 The positive attitudes among both physicians and patients reflect findings from work that predated the pandemic and have been found in numerous other studies done across a variety of settings and health conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Many individuals still prefer to attend in person in the absence of other barriers, as they see this as an important aspect of their assessment and relationship with the provider. 23 , 32 , 33 Providers also may not feel confident in their ability to accurately assess, diagnose, and manage illness in the absence of visual cues. 31 Interestingly, we saw some individuals feel that virtual was superior for certain health needs while others felt it was inferior for the same conditions (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation